Georgia Economic Report, October 2013 : Seeking Effective Policies - World Bank (World Bank, Washington, DC, 2017)
This economic report records the economic activities of Georgia for the year 2013. The growth slow-down in 2013, largely viewed as temporary, reflected to a large extent policy uncertainty that began with the late-2012 parliamentary elections and is expected to last until the October 2013 Presidential elections, and attempts by the new government to trim public investment spending. In the absence of a clear communications strategy and a well-structured development strategy that elaborated the government’s policy direction, a weakening of consumer and investor confidence since November 2012 along with a cut in public investment spending, contributed to slower growth. Both tax and non-tax revenues fell behind budget estimates in the first half of the year reflecting the economic slowdown. The revenue shortfall was driven by a drop in VAT on imports. Demand for imported investment goods has been particularly weak. The external position of the country improved, as imports declined significantly, mainly because of lower demand generated by public investment spending. Commodity imports fell by 19 percent while exports rose 8 percent during the first six months of 2013. Credit growth softened as demand for loans declined even in the face of cuts in the Central Bank rate. The twelve month increase in credit slowed to 12 percent by July 2013 from 24 percent in July 2012. Slower lending and higher deposits have led to excess liquidity in the system.